(3GdeDGeQGJ GdSjGSjI h GdOSGFS HGdOhdI GdHjRfWjI Ref GdEeHQGWhQ ejNGFjd GdKGdK (B842-867(3e(B: s (3ai VhA cJGH GdeDQN GdHjRfWi LfSjhS (B/ s - (3QMeI eMeO YjSis; (3MGeO RjGf ZGfe (B: s ((3GdbGgQI (B: s (3QMeI eMeO YjSi (B: s, 2021)
(3JeKd aJQI Mce GdEeHQGWhQ ejNGFjd GdKGdK (B(842-867(3e(B) (3CcKQ aJQGJ GdOhdI GdHjRfWjI GeJdGA HGdeDGeQGJ GdSjGSjI h GdOSGFS(B. (3h jYhO Pdc Edi eLehYI ef GdbGOI GdSjGSjjf h QLGd GdOjf GdPjf GdJahG Mhd GdEeHQGWhQ h cGf gege GdChd GdhUhd Edi GdSdWI(B: (3dPdc CNPhG jMjchf dHYVge GdHYV eNJda GdeDGeQGJ h GdOSGFS(B. (3h NdGd Jdc GdaJQI XgQJ YOI TNUjGJ dYHJ OhQG cHjQG ai SjGSI GdOhdI GdHjRfWjI(B: (3eKd GdhRjQ GdChd (B"(3KjhcJjSJhS(B" (3h (B"(3HQOGS(B" (3NGd GdEeHQGWhQ(B: (3h GdHWQjQc ahJjhS GdPi cGf CTgQ YdeGA YUQg(B. (3h HGdQZe ef Cf aJQI Mce ejNGFjd GdKGdK TgOJ GdYOjO ef GdeDGeQGJ; EdG Cf YgOg jYJHQ GdHOGjI GdMbjbjI ddJbOe h GdEROgGQ ai GdEbJUGO h GdYde h GdKbGaI(B: (3HGdEVGaI Edi chfg GdHhGHI GdJi YHQJ efgG GdCSQI GdebOhfjI MGUOI KeQI GdQNGA h GdJbOe(B: (3HYO Cf Je HPQge Ref ejNGFjd GdKGdK ecedI HgG GdYUQ GdPgHi ddEeHQGWhQjI GdHjRfWjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdJGQjNs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdOhdI GdHjRfWjIs; (3OSGFSs; (3eDGeQGJs